PENANGANAN ANAK ADHD (ATTENTION DEFICIT HIPERACITIVITY DISORDER) DI MI AMANAH TANGGUNG TUREN - Sari , Aisah Novia; Rohmawati, Afifatu (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2020)
The process of handling ADHD children properly through a form of cooperation built by stakeholders in an educational institution. Qualitative-descriptive research methods (case studies). The results of this research include (1) the process of handling ADHD children through early identification as an effort to reduce the symptoms of ADHD. (2) The role of the teacher in handling ADHD children by showing the pattern of care given by the teacher to children in school. (3) The role of parents in handling ADHD children by showing parenting from parents when at home through a balanced interaction with how to communicate (face to face). (4) The form of collaboration between parents and teachers that can be seen from the intensity of communication through social media or electronic media and letters in evaluating the development of ADHD children. This research can be concluded that the handling of ADHD children through early identification, parenting techniques of teachers and parents as a form of communication to children and the cooperation of teachers and parents